Strong religions and challenges of globalization - Ramos, Christine Carmela R. (The journal of contemporary issues in business and government, 2021)
The paper seeks a comprehensive philosophical understanding of "fundamentalism." Often discriminately associated with the Muslims vis-à-vis terrorism, the paper might eventually be of use to clarify the relationship between Muslims and Christians, as well as with other denominations. The author believes that the philosopher should be alarmed to what the media call the new level of "commodity fetishism" presents to the rest of the world toward (or against) a particular religion, and should rather maintain open roads to dialogue as well as an honest examination of one's own beliefs. The research covers cultural as well as social issues shaping religion and more importantly, favors ideas over ideology in its discussions. Sadly enough, fundamentalism is itself a challenge, far more difficult to understand, nonetheless, the paper highlights fundamentalism in discussing and analyzing strong religions, the question of violence, and enclave culture. The methodology is based on analysis, observations, and insights entwined with the comparison of religions. This article does not just aim to limit itself to a particular dialogue between the Muslim and (or versus) Christianity, but would also attempt to include other beliefs of other parts of the world that would be as essential in comprehending larger issues about one's faith. The paper places the bottom line over the higher ideals of fundamentalists empowering themselves by serving as an authority for a united front in bringing about a religious renaissance amidst the fast-changing realities of the 21st century. Only by overcoming distrust and discrimination, as well as maintaining inter-faith dialogues can an authentic path towards peace, moral and social recovery could be realized.